The Retreat of Positivistic Corporate Social Responsibility, the Rise of Sensemaking and Reflexive Organization Change, a Rhetoric Analysis: The Case of Volkswagen - Teck, Tan Seng; Yew, Lim Kim; Hee, Ong Choon; Fei, Goh Chin; Kowang, Tan Owee (International Journal of Psychosocial Rehabilitation, 2020)
The world has witnessed corporate scandals of monstrosity magnitude. The Enron Scandal, the Nike Sweatshop scandal and the recent Johnson and Johnson baby talc woes are some dishonours that have reshaped the business world and triggered many to reflect the importance of business ethics. Indeed, supranational and national movements such as the Global Reporting Initiatives have responded to these scandals by imposing stricter corporate reporting to instill greater transparency and responsibility. Ironically, despite unwavering efforts, corporations are still blatantly flouting regulations. The Volkswagen “diesel dupe” crisis is a stark reminder of the inherent weakness of current regulations. Despite Volkswagen’s staunch adherence to those stringent reporting guidelines, they breached ethics to the core, creating a tsunami of vehicle recalls, massive social, political and legal repercussions. Volkswagen perfect smart device is a “creative destruction” that challenged the fundamental usefulness of corporate reporting. Corporate Social Responsibility has evolved tremendously, now taking the form of positivistic reporting patterns. Corporations are measured by their ecological, social and economic performance where they flamboyantly table those data and information to garner stakeholders’ support and legitimacy. However, a pragmatic approach towards corporate social responsibility is self-defeating. It erodes and dilutes a corporation’s ability to make sense, communicate and adapt to their externalities. Instead, corporations boast of their corporate prowess and social performance. Using Volkswagen as a subject, this study exposes the inherent weaknesses of a positivistic corporate reporting approach to social responsibility. A positivistic approach such as this cannot engender a truthful, honest and open posture in business corporations. Instead, this study exemplifies that a meaningful sensemaking corporate social responsibility instill reflexive organization change and moral transpose within corporations. Using a rhetorical study, this paper underlines the rhetorical changes and metaphor in Volkswagen as they experience the crisis to epitomize that reflexive change and moral transpose in them. This study is novel and greatly enhances previous literatures in corporate social responsibility by instilling an appropriate model to underline these momentous changes and moral transformations in Volkswagen.